DEVELOPMENT OF REQUIREMENTS FOR INFORMATION SYSTEMS FOR ACCOUNTING OF FIXED ASSETS - Samadov Sevinchbek (Bright Mind Publishing, 2025)
The article explores the evaluation of information systems and technologies used for accounting fixed assets within the framework of digital transformation, highlighting areas for improvement. It examines specialized modules that enable the automation of core functions in fixed asset accounting systems. Additionally, the article presents key recommendations for enhancing the development of these information systems.
Keywords: Digital transformation, fixed asset accounting, information system, requirements, artificial intelligence, machine learning, database, requirements, automation, financial reporting.